2003
DOI: 10.1046/j.1432-1033.2003.03877.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of DAPI with individual strands of trinucleotide repeats

Abstract: The structural changes produced by the minor-groove binding ligand DAPI (4¢,6-diamidine-2-phenylindole) on individual strands of trinucleotide repeat sequences were detected by electrophoretic band-shift analysis and related to their effects on DNA replication in vitro. Among the 20 possible single-stranded trinucleotide repeats, only the T-rich strand of the AATAEATT triplet exhibits an observable fluorescence band and a change in electrophoretic mobility due to the drug binding. This is attributable to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Consistent with this, a typical expansion feature of AAT•TTA triplet repeats was found in an in vitro amplification assay [9], [10], [13], [14], [15], [16], [17], [18]. Moreover, in human populations similar instabilities of AAT•TTA triplet repeats were recently found to be associated with the high IgE blood syndrome in Chinese children [19], with schizophrenia [20], [21], cocaine addiction [22], and with the high prevalence of depression in adult Parkinson's disease patients [23].…”
Section: Introductionsupporting
confidence: 77%
“…Consistent with this, a typical expansion feature of AAT•TTA triplet repeats was found in an in vitro amplification assay [9], [10], [13], [14], [15], [16], [17], [18]. Moreover, in human populations similar instabilities of AAT•TTA triplet repeats were recently found to be associated with the high IgE blood syndrome in Chinese children [19], with schizophrenia [20], [21], cocaine addiction [22], and with the high prevalence of depression in adult Parkinson's disease patients [23].…”
Section: Introductionsupporting
confidence: 77%
“…The sequence is A-T rich and may have unusual helical parameters that could diminish MMR. For example, sequences containing larger numbers of ATT repeats can form a non-hydrogen bonded structure [37], and can be induced into hairpins by the DNA minor groove binding ligand DAPI (4′,6-diamidino-2-phenylindole) [38], [39]. Triplet repeat sequences can form non-B-DNA structures that bind MMR proteins (reviewed in [30]), and they are often associated with genome instability (reviewed in [40]), albeit characterized by indels rather than base substitutions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that DAPI stalls replication of the (AT T) 10 template by the Klenow fragment of DNA polymerase I, presumably due to hairpin formation. 168 This demonstrates that drug binding to mismatch sites can result in conformation changes of the DNA strands, leading to modulation of biological properties.…”
Section: Melamine-intercalator Conjugates and Analoguesmentioning
confidence: 99%